ANALISIS RESOURCE LEVELING MENGGUNAKAN METODE BURGESS PADA PROYEK GUDANG BORNEO BUSINESS ICON KUBU RAYA - Ayu Putri, Prabu Indra Swari; Arpan, Budiman; Mulyani, RR. Endang (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2017)
Materials and equipment needs of the project took the largest portion amounting to about 60%, while the needs of the labor ranged between 25%-30% of the total project cost. However it is difficult enough to suppress the cost of materials and equipment expenses, so the labor needs of control was undertaken by resource leveling as an alternative to pressing the project costs. Resource leveling is one of the efforts in managing projects in order to avoid sharp fluctuations and to make labor can be empowered in an efficient and effective manner. The purpose of resource leveling is to obtain optimum utilization of labor and labor costs as well as to avoid the time where labor needs to be very high or very low. The method used is descriptive quantitative. In analyzing the data, this research uses Burgess method or the sum of square method (Z) with a system of reverse late start and with the help of software. Labor leveled is worker, carpenter, welder, and head of worker. Worker, welder, and head of worker has decreased the value of Z, decreased in the maximum amount of labor, increased in the minimum amount of labor, as well as decreased in the maximum wage per week. As for the carpenter, the Z value has decreased but the minimum and maximum amount has not changed, so that the maximum wage per week also remain, both before and after leveling. Although the calculation of resource leveling by applying the Burgess method is quite simple, yet very effective in reducing fluctuations in the use of labor so getting new labor scheduling more evenly. Keywords: resource leveling, labor, Burgess Method, wage